An electrostatic scheme realizing the complete interception of fog droplets by corona discharge-induced ion wind. (6th April 2021) - Zhang, Ming; Li, Dingchen; Li, Chuan; Li, Jiawei; Wang, Pengyu; Liu, Zhi; Xu, Qiuyu; Yang, Yong; Yu, Kexun; Zheng, Bo; Wang, Yiju; Liu, Yizhou; et al.
Abstract: The interception of fog is of great significance for industrial production and human activities. Owing to the simple structure and convenient installation, the fog mesh is widely adopted to intercept droplets in industrial and practical applications. However, the interception mechanism and requirements in high droplet concentration, result in a low inherent interception efficiency. Therefore, a novel method that can completely intercept fog droplets and enhance the local droplets number concentration by changing the direction of fog entering the electric field by using ion wind, is put forward in this paper. Experimental results show that the introduction of ion wind can improve the interception efficiency to reach nearly 100%. In addition, the droplets number concentration near the ground mesh electrode can reach two times of the initial number concentration. The experiment also studied the optimal interception voltage under different electrode spacing, which is meaningful to guide the industrial application of using ion wind to intercept droplets. This method can completely intercept the fog droplets, and further reduce the lower limit of the fog concentration required by the fog mesh to intercept droplets.